Decreasing dependency through self-reliance: Strengthening local economies through Community Wealth Building - Julia Eder (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2021)
The impact of the global financial crisis of 2007ff. led peripheral communities in the USA and in the UK such as Cleveland and Preston to question their unsustainable, outward-oriented and socially excluding development model. As a consequence, they adopted Community Wealth Building (CWB) as a new and fundamentally different local development strategy. This strategy has been analysed in case studies or in comparison with other contemporary progressive movements, initiatives and strategies, for example cooperative movements or the foundational economy. However, this paper argues that CWB shows equally interesting parallels with historical debates and practices of 'self-reliance' which different actors developed from the 1960s to the 1980s (mainly) in the Global South, and which are worth being studied more in detail. Thus, this paper examines to what extent CWB resembles older self-reliance approaches and how community wealth building could benefit from engaging with the theoretical foundations of the earlier debates. The central thesis is that the commonalities are more relevant than the differences and that, due to this, the actors associated with CWB could benefit from engaging with the legacy of self-reliance to complement the theoretical foundation of their approach. Methodologically, the paper draws on an analysis of policy documents, newspaper articles, and the insights from four exploratory interviews with policy advisers and politicians involved with CWB.
Keywords: 330